Serotonin-related rodent models of early-life exposure relevant for neurodevelopmental vulnerability to psychiatric disorders - Adjimann, Tamara Sol (2021)
Mental disorders including depression and anxiety are continuously rising their prevalence across the globe. Early-life experience of individuals emerges as a main risk factor contributing to the developmental vulnerability to psychiatric disorders. That is, perturbing environmental conditions during neurodevelopmental stages can have detrimental effects on adult mood and emotional responses. However, the possible maladaptive neural mechanisms contributing to such psychopathological phenomenon still remain poorly understood. In this review, we explore preclinical rodent models of developmental vulnerability to psychiatric disorders, focusing on the impact of early-life environmental perturbations on behavioral aspects relevant to stress-related and psychiatric disorders. We limit our analysis to well-established models in which alterations in the serotonin (5-HT) system appear to have a crucial role in the pathophysiological mechanisms. We analyze long-term behavioral outcomes produced by early-life exposures to stress and psychotropic drugs such as the selective 5-HT reuptake inhibitor (SSRI) antidepressants or the anticonvulsant valproic acid (VPA). We perform a comparative analysis, identifying differences and commonalities in the behavioral effects produced in these models. Furthermore, this review discusses recent advances on neurodevelopmental substrates engaged in these behavioral effects, emphasizing the possible existence of maladaptive mechanisms that could be shared by the different models.